Perspectives of sensory goals in therapeutic landscape: a review / Nuraimi Amalina Abu Bakar and Nor Fadzila Aziz - Abu Bakar, Nuraimi Amalina; Aziz, Nor Fadzila (Universiti Teknologi MARA, Perak, 2024)
Sensory elements play a crucial role in therapeutic landscapes, which influence individual health status in potentially positive or negative ways. The aim of this article is to explore the notion of this sensory element in therapeutic landscape that has been studied in the existing literature from 2000 to 2023 through SCOPUS database. Review of literature consisted four (4) phases which were identification, screening, eligibility, and inclusion. Then, the synthesis focused specifically on perspectives of sensory goals formed that are related to various aspects of human health and well-being. The perspectives of related literature were collected and discussed. In summary, sensory goals are divided into four (4) aspects of well-being. Accordingly, physiological health was observed as the most important thing to achieve during sensory experience in therapeutic landscape. Followed by psychological health, social interaction, and finally socio-ecological relationships. Through this process, it is clear that creating an environment should consider and cater to the users’ specific sensory goals for different targeted populations based on their unique profiles and therapeutic needs in order to optimize the outcome possibilities.